Organizing for community-based natural resources management - Campbell, Bruce M.; Shackleton, S. (2002)
There has been a move to decentralize natural resource management (NRM) throughout southern Africa but this has taken many forms, resulting in different organizational structures. Fourteen case studies from eight countries can be classed into four types: district-level organizations, village organizations, organizations outside the state hierarchy, and corporate organizations at the village level. Attitudes towards district-level schemes amongst local people are generally negative. The greater the authority village organizations receive the more likely they are to succed. In the cases of corporate organizations, local residents have received user or proprietary rights over resources. Such cases indicate the best chances of community-based natural resources management (CBNRM) being successfull. The impact of private sector stakeholders can be positive or negative depending on the institutional arrangements in place. Many of the cases have demonstrated the key role that external facilitation plays in building the capacity of local organizations. Traditional leaders have continued to play a role in NRM, with varying degree of authority and control.